The Right to be Forgotten: Protecting Emergency Contact in the Reform of Personal Data Protection Policy in Indonesia - Intani, Aulia Anugrah; Syafira, Ade Afni (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2025)
This article analyzes concern regarding the massive development of online lending applications in Indonesia. The government should make that invention as one of the priority focuses for protecting Indonesia’s citizen. Various studies and regulations have been made by the government to protect online loan users. Unfortunately, there is one party that still needs to be prioritised for protection in Indonesia, which is the emergency contacts of online loan application users. Emergency contacts need legal protection regarding their data used by borrowers as collateral if they default. Indonesian law is inadequate inthisregard.Therefore, innovations are needed regarding the applicable regulations and concepts to be able to protect emergency contacts’ data. The method used in this paper is literature review. The result of this study found that a more comprehensive regulation and implementation of Right to be Forgotten is needed to keep upwith the rapid technological developments in the field of financial technology. The results emphasise the importance of personal data protection not only for borrowers, but also for emergency contacts. The reason for this is due to the increasing number of data breach cases. Ultimately, this research found that reforms by applying data protection principles are essential to protect the parties in online loan service providers